2019
DOI: 10.1177/0954410019836916
|View full text |Cite
|
Sign up to set email alerts
|

Extraction process of charged droplets in ultrasonic electric propulsion system: An experimental study

Abstract: As a novel propulsion technology, ultrasonic electric propulsion is mainly applied to micro-satellite platforms (<10 kg). In this work, effects of vibration frequency and typical operating conditions on extraction process of charged droplets in ultrasonic electric propulsion are investigated by an ultra-high speed imaging technique. A long-distance microscope coupled with an ultra-high speed camera (NAC HX-6) is also used. A solution of formamide and lithium chloride is employed as propellant. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The formation mechanism of the multiple-emission modes is the combination effects of the thickness of liquid film, formation of CSWs, and electrostatic effects. Though the images of the partial formation of CSWs without applying an electric field were captured in the previous work [20], it cannot be concluded that the partial formation of CSWs results in partial emission plumes.…”
Section: Partial Emission Of Charged Droplets On the Right Side Of Th...mentioning
confidence: 95%
See 2 more Smart Citations
“…The formation mechanism of the multiple-emission modes is the combination effects of the thickness of liquid film, formation of CSWs, and electrostatic effects. Though the images of the partial formation of CSWs without applying an electric field were captured in the previous work [20], it cannot be concluded that the partial formation of CSWs results in partial emission plumes.…”
Section: Partial Emission Of Charged Droplets On the Right Side Of Th...mentioning
confidence: 95%
“…In contrast, the other two-thirds of the emission surface on the right side does not emit droplets. This phenomenon is first revealed by the high-speed imaging system, though experimental results have indicated partial formation of CSWs on the emission surface [20]. The DPEs imply two possibilities regarding the liquid film: first, the liquid film on the emission surface has an uneven thickness, which causes the DPEs on the emission surface; second, even though the liquid film covers the entire emission surface, the CSWs only form on a portion of it, which causes the DPEs in the UEP system.…”
Section: Partial Emission Of Charged Droplets On the Left Side Of The...mentioning
confidence: 98%
See 1 more Smart Citation